Stock Status for Sustainable Management of Small Pelagic Fish Targeted in Minahasa Peninsula Waters - Lohoo, Anneke V.; Silloy, Fanny; Sitanggang, Effendie Panghutan (Jurnal Ilmiah PLATAX, 2026)
This study aims to determine the size of pelagic fish at first sexual maturity as a basis for analyzing the balance between immature and mature fish in the catch. The mesh size of the fishing gear is also assessed to determine whether it aligns with the height of mature fish. Both of these factors are crucial for ensuring sustainable management of small pelagic fish targeted in Minahasa Peninsula waters. Monitoring of small pelagic fish stocks can be conducted by analyzing the length-weight and gonad maturity levels of small pelagic fish. The conditions at capture are compared to the minimum size, maximum size, and size at gonad maturity of fish in specific waters. The analysis in this study compares fish sizes from two fishing grounds: Sulawesi waters (TPI Tumumpa) and Maluku waters (TPI Aertembaga). This research provides an overview of small pelagic fish stocks in terms of sustainability. This aligns with the research areas of excellence at Sam Ratulangi University. Keywords: pelagic; sustainable; sexual maturity; fish Abstrak Penelitian ini bertujuan menentukan ukuran ikan pelagis pertama kali matang kelamin sebagai dasar menganalisis keseimbangan jumlah ikan berukuran belum dan sudah matang kelamin pada ikan hasil tangkapan. Menilai ukuran mata jaring pada alat tangkap apakah sudah sesuai dengan ukuran tinggi badan ikan yang sudah matang kelamin. Kedua hal di atas penting agar bisa menjamin kegiatan pengelolaan berkelanjutan pada ikan pelagis kecil sebagai ikan target di perairan Minahasa Peninsula. Pemantauan stok ikan pelagis kecil dapat dilakukan dengan analisis ukuran panjang-berat dan tingkat kematangan gonad dari ikan pelagis kecil. Kondisi saat tertangkap akan dibandingkan dengan ukuran minimum ikan, ukuran maksimum ikan, dan ukuran saat matang gonad ikan di perairan tertentu. Analisis pada penelitian ini dilakukan dengan membandingkan ukuran ikan dari dua daerah penangkapan, yakni perairan Sulawesi (TPI Tumumpa) dan perairan Maluku (TPI Aertembaga). Penelitian ini menghasilkan gambaran stok ikan pelagis kecil dalam kaitan dengan kebelanjutannya. Hal ini sesuai dengan bidang unggulan penelitian dari Universitas Sam Ratulangi. Kata kunci: pelagis; berkelanjutan; matang kelamin; ikan